Practical information on electrochemical corrosion of water pipelines - Dąbrowski, Wojciech; McGarity, Arthur (Instal, 2021)
Some aspects of drinking water ductile iron pipeline’s electrochemical corrosion are discussed in this paper. We include: the impact of water parameters on its corrosivity, the relationships between the cement mortar lining and head loss to flow, pipeline diameter, and the total alkalinity of water, lifetime of the cement mortar lining. The discus sion is limited strictly to some practical remarks with little theoretical background.
Keywords: electrochemical corrosion; corrosivity of water; mortar lining of pipes